Public space as a tourism object: the existence of Pakui Sayang Park in Makassar City - Ahmadin Ahmadin (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The existence of city parks today does not only serve as an icon of adding beauty, but has become a public space and a tourist attraction that is busy with people. Visitors who take advantage of city parks are not only local residents, but also residents from other regions or parties who happen to be visiting a city for certain interests. This article examines one of the public spaces that has become a tourist attraction in Makassar City, namely Pakui Sayang Park. This park is always crowded with visitors, especially in the afternoon, on Sundays and other holidays. In terms of public space criteria, Pakui Sayang Park fulfills these requirements, namely providing good quality service to users, high levels of visitor activity, giving a variety of meanings and significance to the audience, and being very accessible because it is located on the side of the main road in the city center. The results of the study show that Pakui Sayang Park as a public space functions as: (1) sports facilities, such as gymnastics, jogging tracks, tennis, and others; (2) entertainment facilities, such as live music and various events; (3) a place to hang out supported by seats under shady trees; and (4) culinary tours that provide various special menus.